Metabolomics: importance of experimental design to data acquisition 2 - Yanes, Oscar (Henry Stewart Talks, 2018)
Pre-processing data analysis, Metabolomics bottleneck & the “cocktail party problem”, From raw data to metabolites IDs, Challenges in GC/MS & LC/MS, Metabolic annotation examples, LC/MS workflow, Searching databases, Hypothesis & experimental validation, “Static”, “Dynamic” & "Integrated" pictures of metabolomics